The Politics and Institutions of Project Approval - a Critical-Constructive Comment on the Theory of Strategic Misrepresentation - Osland, Oddgeir; Strand, Arvid (European Journal of Transport and Infrastructure Research, 2010)
This article addresses theoretical and methodological explanations of miscalculations of costs and benefits in large infrastructure projects. In particular the focus is on the most influential theoretical contribution in this area, labeled ‘the theory of strategic misrepresentation’, a theory strongly associated with the work of Bent Flyvbjerg. The theory’s major explanation of cost overruns is that the registration and representation of data and the calculations of costs and benefits are made by planners in organisations that have economic interests in the results. They work in a context were they compete for scarce public resources, and in which lying pays off in the end. The result is, as Flyvbjerg expresses it, the ‘survival of the unfittest’. It is not the best projects that are built, but the most misrepresented ones. This theory, with its focus on the institutional context and incentive structures, represents a major step forward compared to the solely methodological explanations. However, it has several shortcomings both in theoretical and methodological terms. Methodologically, the research has not the design necessary for validating the conclusion of ‘the survival of the unfittest’. Theoretically, the framework does not offer any variation on the institutional variable nor when it comes to variation in planners (actors) motives and rationality. Hence, there is a need for a broader theoretical framework. We conclude our article by sketching such a framework, an institutional approach grounded in sociological theory, as well as applying it to Norwegian transport planning. The Norwegian research in this area does not support the thesis that project approval is a result of planners’ strategic actions. More often it is an outcome of institutions where politicians play a key role at all levels and stages of the planning process, often neglecting planners’ analyses and recommendations.